Adjunctive agomelatine therapy in the treatment of acute bipolar II depression: a preliminary open label study - Fornaro M (Dove Medical Press, 2013)
Michele Fornaro,1 Michael J McCarthy,2,3 Domenico De Berardis,4 Concetta De Pasquale,1 Massimo Tabaton,5 Matteo Martino,6 Salvatore Colicchio,7 Carlo Ignazio Cattaneo,8 Emanuela D'Angelo,9 Pantaleo Fornaro61Department of Formative Sciences, University of Catania, Catania, Italy; 2Department of Psychiatry, Veteran's Affairs San Diego Healthcare System, 3University of California San Diego, La Jolla, CA, USA; 4Department of Mental Health, Psychiatric Service of Diagnosis and Treatment, "ASL 4", Teramo, Italy; 5Department of Internal Medicine and Medical Specialties, University of Genova, Genoa, Italy; 6Department of Neurosciences, Section of Psychiatry, University of Genova, Genoa, Italy; 7Unit of Sleep Medicine, Department of Neuroscience, Catholic University, Rome, Italy; 8National Health System, "ASL 13", Novara, Italy; 9National Health System, "ASL 3", Genoa, ItalyPurpose: The circadian rhythm hypothesis of bipolar disorder (BD) suggests a role for melatonin in regulating mood, thus extending the interest toward the melatonergic antidepressant agomelatine as well as type I (acute) or II cases of bipolar depression.Patients and methods: Twenty-eight depressed BD-II patients received open label agomelatine (25 mg/bedtime) for 6 consecutive weeks as an adjunct to treatment with lithium or valproate, followed by an optional treatment extension of 30 weeks. Measures included the Hamilton depression scale, Pittsburgh Sleep Quality Index, the Clinical Global Impression Scale–Bipolar Version, Young Mania Rating Scale, and body mass index.Results: Intent to treat analysis results demonstrated that 18 of the 28 subjects (64%) showed medication response after 6 weeks (primary study endpoint), while 24 of the 28 subjects (86%) responded by 36 weeks. When examining primary mood stabilizer treatment, 12 of the 17 (70.6%) valproate and six of the 11 (54.5%) lithium patients responded by the first endpoint. At 36 weeks, 14 valproate treated (82.4%) and 10 lithium treated (90.9%) subjects responded. At 36 weeks, there was a slight yet statistically significant (P = 0.001) reduction in body mass index and Pittsburgh Sleep Quality Index scores compared to respective baseline values, regardless of mood stabilizer/outcome. Treatment related drop-out cases included four patients (14.28%) at week 6 two valproate-treated subjects with pseudo-vertigo and drug-induced hypomania, respectively, and two lithium-treated subjects with insomnia and mania, respectively. Week 36 drop outs were two hypomanic cases, one per group.Conclusion: Agomelatine 25 mg/day was an effective and well-tolerated adjunct to valproate/lithium for acute depression in BD-II, suggesting the need for confirmation by future double blind, controlled clinical trials.Keywords: bipolar disorder type-II, acute bipolar depression, agomelatine, adjunctive treatment